Description of Acanthonavis deflexa gen. et sp. nov. (Hemiptera: Aleyrodidae) from the Nicobar Island, India, and generic re-definition of Editaaleyrodes David - Dubey, Anil Kumar (Zootaxa, 2022)
A new whitefly genus and species, Acanthonavis deflexa gen. et sp. nov. are diagnosed and discussed with description of dimorphic puparia, third and second instars collected on the Nicobar Island, India. Puparia of the new genus differ from all other genera in demarcated subventral area and deflexed submargin, and from an allied genus Editaaleyrodes David in lacking polygonal markings in the thoracic tracheal furrows, and geminate pores, and in having subventral area demarcated from the submargin. The whitefly genus Editaaleyrodes is re-defined and diagnosed for puparial characters through examination of its type species, Editaaleyrodes indicus David. Several previously undescribed morphological characters of E. indicus are discussed and figured. Line drawings and microphotographs of habitus on leaf surface of the new species, are provided.